PUMPA - THE SMART LEARNING APP

Take a 10 minutes test to understand your learning levels and get personalised training plan!

Download now on Google Play
Let us expand some of the cubic terms using its identities.
Write the cube in expanded form.
 
1. \((2x+3y)^3\)
 
Let us use the identity, \((a+b)^3\)\(=\) \(a^3+3a^2b+3ab^2+b^3\).
 
Comparing \((2x+3y)^3\) with \((a+b)^3\), we have \(a=2x\) and \(b=3y\).
 
Substitute the values in the formula.
 
\((2x+3y)^3\) \(=\) \((2x)^3\)\(+3(2x)^2(3y)\)\(+3(2x)(3y)^2\)\(+(3y)^3\)
 
\((2x+3y)^3\) \(=\) \(8x^3\)\(+(2\times 4\times 3)x^2y\)\(+(3\times 2\times 9)xy^2\)\(+27y^3\)
 
\(= 8x^3+24x^2y+54xy^2+27y^3\)
 
 
2. \((5x-7y)^3\)
 
Let us use the identity, \((a-b)^3\)\(=\)\(a^3-3a^2b+3ab^2-b^3\).
 
Comparing \((5x-7y)^3\) with \((a-b)^3\), we have \(a=5x\) an d\(b=7y\).
 
Substitute the values in the formula.
 
\((5x-7y)^3\) \(=\) \((5x)^3\)\(-3(5x)^2(7y)\)\(+3(5x)(7y)^2\)\(+(7y)^3\)
 
\((5x-7y)^3\) \(=\) \(125x^3\)\(-(3\times 25\times 7)x^2y\)\(+(3\times 5 \times 49)xy^2\)\(+343y^3\)
 
\((5x-7y)^3\) \(=\) \(125x^3\)\(-525x^2y\)\(+735xy^2\)\(+343y^3\)
 
 
4. \((4y+5)(4y+3)(4y-7)\)
 
Let us use the identity, \((x+a)(x+b)(x+c)\) \(=\) \(x^3+(a+b+c)x^2\)\(+(ab+bc+ca)x\)\(+abc\)
 
Comparing \((4y+5)(4y+3)(4y-7)\) with \((x+a)(x+b)(x+c)\), we have \(x=4y, a=5, b=3\) an d\(c=-7\).
 
Substitute the known values.
 
\((4y+5)(4y+3)(4y-7)\) \(=\) \((4y)^3\)\(+(5+3-7)(4y)^2\)\(+((5\times 3) + (3\times -7) +(-7\times 5))(4y)\)\(+5 \times 3 \times -7)\)
 
\((4y+5)(4y+3)(4y-7)\) \(=\) \(64y^3+16y^2\)\(+(15-21-35)(4y)-105\)
 
\((4y+5)(4y+3)(4y-7)\) \(=\) \(64y^3+16y^2\)\(-164y-105\)
 
Example:
Look for the following cases where we used the identities.
 
1. Expand \((y-5)^3\) using identity.
 
The above expression is in \((a-b)^3\) form.
 
We have the identity, \((a-b)^3\)\(=\)\(a^3-3a^2b+3ab^2-b^3\).
 
Substitute \(a = y\) and \(b = 5\) in the formula.
 
y53=y33(y)2(5)+3(y)(5)253
 
y53=y315y2+75y125
 
 
2. Evaluate \(103^3\) using identity.
 
\(103^3\) \(=\) \((100+3)^3\)
 
The above expression is in \((a+b)^3\) form.
 
We have the identity, \((a+b)^3\) \(=\) \(a^3+3a^2b+3ab^2+b^3\)
 
Substitute \(a =100\) and \(b = 3\) in the formula.
 
100+32=1003+3(100)2(3)+3(100)(3)2+33
 
=1000000+(3×10000×3)+(3×100×9)+27
 
=1000000+90000+2700+27
 
=1092727